2016
DOI: 10.1007/s13399-016-0204-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of coated olivine on the conversion of intermediate products from decomposition of biomass tars during gasification

Abstract: Steam gasification of solid biomass in dual fluidized bed systems is a suitable technology for the production of chemicals, fuels for transportation, electricity, and district heating. Interaction between biomass ash and bed material leads to the development of Ca-rich bed particle layers. Furthermore, incomplete decomposition of biomass leads to the formation of tar components; among these are stable intermediate products such as 1H-indene and stable gaseous hydrocarbons such as methane. In this work, the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 34 publications
4
43
0
Order By: Relevance
“…Olivine forms Carich layers, which improve the catalytic activity, via the interaction of the bed material particles with the woody biomass ash on the surface of the particles after days of operation [43,44]. Additionally, Wagner et al [45] and Kuba et al [16] found out that also the fuel ash has an impact on the product gas composition due to an increased catalytic activity caused by layer formation. However, for the presented test campaigns, it was not possible to run the pilot plant continuously for a few days to simulate the operation of an industrial-sized gasification plant.…”
Section: Validation Of Process Data With Ipsepromentioning
confidence: 99%
See 1 more Smart Citation
“…Olivine forms Carich layers, which improve the catalytic activity, via the interaction of the bed material particles with the woody biomass ash on the surface of the particles after days of operation [43,44]. Additionally, Wagner et al [45] and Kuba et al [16] found out that also the fuel ash has an impact on the product gas composition due to an increased catalytic activity caused by layer formation. However, for the presented test campaigns, it was not possible to run the pilot plant continuously for a few days to simulate the operation of an industrial-sized gasification plant.…”
Section: Validation Of Process Data With Ipsepromentioning
confidence: 99%
“…Kuba et al found out that the WGS reaction is a follow-up reaction of the steam reforming reaction, where part of the produced CO during steam reforming is converted into H 2 and CO 2 in the presence of H 2 O. [16] Eq. 3 describes the endothermic steam reforming of hydrocarbons and is especially important for steam gasification.…”
Section: Introductionmentioning
confidence: 99%
“…Mauerhofer et al tested K-feldspar (0.87 kg kg −1 K-feldspar, 0.07 kg kg −1 Na-feldspar) as a bed material for DFB steam gasification and observed a low catalytic activity, compared to olivine and calcite [40]. Selective tests of the catalytic activity showed no activity regarding the WGS reaction [25] and tar reduction [41], though it was possible to observe an activation over time during DFB steam gasification with an ash-rich fuel mixture of bark, straw, and chicken manure [24]. The influence of phosphorus, originating from chicken manure, on layer formation on K-feldspar was studied for combustion and steam gasification atmosphere by Wagner et al [27].…”
Section: Introductionmentioning
confidence: 99%
“…[12,13]. However, the mechanisms of polycyclic aromatic hydrocarbon (PAH) formation are understood in terms of the chemistry of gas-phase radicals [14][15][16], so it is likely that the ash-coated olivine can alter the gas-phase chemistry both indirectly, as a result of heterogeneous catalysis [11], as well as directly owing to the inhibitory effects of alkali on the formation of tar and soot [12,13]. Based on the existing literature [11,12,[17][18][19], Figure 1 depicts the potential interplays between heterogeneous (lower box) and…”
Section: Introductionmentioning
confidence: 99%
“…homogeneous (upper box) interactions between the ash-layered olivine and the tar chemistry. [11,12,[17][18][19] . HC' represents a generic hydrocarbon, and HC˙ represents a generic hydrocarbon radical.…”
Section: Introductionmentioning
confidence: 99%